Structural, Magnetic, and Magneto-Thermal Properties of Rare Earth Intermetallic GdRhIn - Ravinder Kumar; Arrab Ali Maz; Satyendra Kumar Mishra; Sachin Gupta (Sensors, 2024)
We study the structural, magnetic, and magneto-thermal properties of the GdRhIn compound. The room-temperature X-ray diffraction measurements show a hexagonal crystal structure. Temperature and field dependence of magnetization suggest two magnetic transitions—antiferromagnetic to ferromagnetic at 16 K and ferromagnetic to paramagnetic at 34 K. The heat capacity measurements confirm both the magnetic transitions in GdRhIn. The magnetization data were used to calculate isothermal magnetic entropy change and refrigerant capacity in GdRhIn, which was found to be 10.3 J/Kg-K for the field change of 70 kOe and 282 J/Kg for the field change of 50 kOe, respectively. The large magnetocaloric effect in GdRhIn suggests that the material could be used for magnetic refrigeration at low temperatures.